Annular Array Transducer and Matched Amplifier for Therapeutic Ultrasound - SECOMSKI, Wojciech; NOWICKI, Andrzej; WÓJCIK, Janusz; LEWANDOWSKI, Marcin; WALCZAK, Mateusz; TYMKIEWICZ, Ryszard (Archives of Acoustics, 2010)
The use of therapeutic ultrasound continues to grow. A focused ultrasonic wave can increase the tissue temperature locally for the non-invasive cancer treatment or other medical applications. The authors have designed a seven-element annular array transducer operating at 2.4 MHz. Each element was excited by sine burst supplied by a linear amplifier and FPGA control circuits. The acoustic field, generated by a transducer was initially numerically simulated in a computer and next compared to water tank hydrophone measurements performed at 20, 40 and 60 mm focal depth. The results showed good agreement of the measurements with theory and the possibility to focus the ultrasound in the preselected area. The total acoustic power radiated by the annular array was equal to 2.4 W.